Organizational and Managerial Mechanisms for Monitoring the Quality of Education in the Education System of Uzbekistan - Toshmatova Kumush Aliboy qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
This section examines the organizational and managerial mechanisms for monitoring the quality of education within the education system of the Republic of Uzbekistan. In the context of ongoing educational reforms, quality monitoring has become a key instrument for improving governance efficiency, ensuring compliance with state educational standards, and enhancing learning outcomes. The study analyzes the institutional framework, regulatory and legal foundations, and management practices that support education quality monitoring at national and institutional levels. Particular attention is paid to the role of state authorities, internal quality assurance units, and data-driven management tools. The interaction between internal and external quality assurance mechanisms is also explored. The findings indicate that effective organizational structures and feedback-based management processes contribute significantly to continuous quality improvement in Uzbekistan’s education system. At the same time, existing challenges related to institutional capacity and analytical competencies highlight the need for further development of monitoring mechanisms.